A conceptual framework for integrating mental rotation and 3D animation pedagogy / Yi Zhongyao, Mohd Khairulnizam Ramlie and Shafilla Subri - Yi, Zhongyao; Ramlie, Mohd Khairulnizam; Subri, Shafilla (Faculty of Art and Design, 2024)
This conceptual paper introduces a framework exploring the emotive dimensions of spatial learning in college students, employing a quantitative research approach. Integrating the mental rotation method with 3D animation pedagogy, the research aims to elucidate the interplay between emotional learning and spatial visualization enhancement. Quantitative data analysis includes descriptive statistics, independent samples t-tests, and analysis of variance (ANOVA). The framework proposes that this combination can evoke positive emotions, such as engagement and enjoyment, contributing to a more effective spatial learning experience. Findings emphasize the mediating role of emotional engagement in the relationship between pedagogical methods and spatial learning outcomes. Educators are encouraged to consider students' emotional responses, recognizing the potential of positive emotions to enhance mental rotation training within the context of 3D animation. In conclusion, this conceptual framework provides a foundation for further research and practical applications, aiming to optimize spatial learning outcomes in college students.